The impacts associated with having ADHD: an umbrella review - French, Blandine; Nalbant, Gamze; Wright, Hannah; Sayal, Kapil; Daley, David; Groom, Madeleine J.; Cassidy, Sarah; Hall, Charlotte L. (Frontiers in Psychiatry, 2024)
Introduction: Attention Deficit Hyperactivity Disorder (ADHD) affects up to 5% of the population and is characterised by symptoms of impulsivity, hyperactivity and inattention. These symptoms are significantly impairing and carry additional risks for children and adults with ADHD, including negative mental health (e.g. depression), physical health (e.g. obesity) and societal outcomes (e.g. imprisonment, divorce). Very few studies have attempted to synthesise these risks in one publication due to the breadth of evidence published on the adverse outcomes of ADHD. Methods: An umbrella review was performed to identify reviews (systematic, meta-analysis and narrative) that investigate the risks arising from having ADHD. We conducted a narrative synthesis of the findings and conducted a quality review of the included publications. Results: Upon searching five databases, 16,675 records were identified. Of these, 125 reviews met the criteria for inclusion. A narrative synthesis of these findings highlighted three key domains of risks associated with ADHD: mental health, physical health, social and lifestyle. Most reviews were of good and moderate quality. Discussion: This review highlights the many risks associated with having ADHD, beyond its three key symptom domains and the impact of the condition on daily functioning.